Do mal-estar em Freud ao mal-estar em Bauman - Nascimento, Marcio Lima do (2014)
The purpose of this project is to portray a particular trait combination between guilt and fear and establish a connection between the analysis of Freud and Bauman on the notion of ill-being . Our reading of Freud's literature on the ill-being of civilization points to guilt as being a key element in the civilizing project, which transgresses the authenticity of the values of life and leads the subject to live continually immersed in a state of hardship. From this perspective, to be protected of threats of any kind, everyone is bound to sacrifice freedom and convert pleasure into guilt. In a civilized dimension obsessed with security, more freedom is akin to less ill-being. Bauman attempts to analyze the issue from the aspect of uncertainty and undetermination, which according to you are striking features of contemporaneity. According to the author, in the postmodern condition we find a deep lack of certainty, protection and security. The fearfulness is very numerous and inseparable from human life. He presents the foundations of social fears that plague individuals in liquid modernity, seeking to identify their common origins. In his view all that human beings have always sought was happiness and that it could only be obtained through communion between security and freedom, irreconcilable throughout history, incompatible in the modern civilization but apparently viable for consumption.